2020
DOI: 10.21203/rs.3.rs-32379/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Research title on Multilevel Modelling of Time to Death for Under-Five Children: 2016 Ethiopia Demographic and Health Survey, 2019

Abstract: Background: Reducing child mortality is now a global concern. Globally, Under-five child mortality rate was decreased by 58% in 2017. In the 2016 EDHS report, under-five mortality was declined to 60% in Ethiopia in 2016. Methods: The data for the study was obtained from EDHS data conducted in 2016. In the study, we analysed the data using stratified Cox proportional hazard model and multilevel lognormal parametric survival model. Results: From the total of 10,331 under-five children, 635 (6.1%) deaths had occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…29 This result is also higher than what Argawu's study in Ethiopia found, which was 55.4 months. 23 This finding suggests that under-five child survival rates have improved in Ethiopia.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…29 This result is also higher than what Argawu's study in Ethiopia found, which was 55.4 months. 23 This finding suggests that under-five child survival rates have improved in Ethiopia.…”
Section: Discussionmentioning
confidence: 97%
“…According to a multilevel survival study conducted in Ethiopia, children from families with four to six members and more had a reduced probability of passing away before the age of five than those from families with one to three members. 23 A study conducted in rural Ethiopia found that having a larger family size decreased the chance of death among children under the age of five by fifty-six percent. 30 On the other hand, a study by Gebretsadik using the 2011 DHS data in Ethiopia found a direct relationship between family size and mortality among children under the age of five.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations